Self-assembled DNA composite membranes - Won, J; Chae, SK; Kim, JH; Park, HH; Kang, YS; Kim, HS (ELSEVIER, 2005)
Conductive, self-assembled DNA composite membranes supported by a nano-porous polycarbonate substrate were fabricated. The porous polycarbonate support membranes were modified with Sn2+ positive charges to induce effective DNA adsorption. Optimum pore size of 0.1mum and high pore density have been realized for track etched nano-porous polycarbonate membrane in the self-assembly process. Proton conductivity and methanol permeability (10 wt.%) were evaluated to be 8.0 x 10(-2) S/cm and 5.0 x 10(-7) cm(2)/s for 1.6 mg/cm(2) of DNA loading, respectively. The self-assembled DNA composite membranes exhibit excellent proton conductivity, and enhanced mechanical properties with decreased methanol permeability. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: METHANOL TRANSPORT; PROTON; CONDUCTIVITY; FILMS